Covalent organic framework with sulfonic acid functional groups for visible light-driven CO2 reduction. Issue 28 (17th June 2022) - Li, Wanrong; Wang, Qian; Cui, Fuzhi; Jiang, Guofang
Abstract : In this study, covalent organic framework (TpPa–SO3 H) photocatalyst with sulfonic acid function groups was synthesized using a solvothermal method. Abstract : In this study, a covalent organic framework (TpPa–SO3 H) photocatalyst with sulfonic acid function groups was synthesized using a solvothermal method. The morphologies and structural properties of the as-prepared composites were characterized by X-ray diffraction, infrared spectroscopy, ultraviolet-visible diffuse reflectance spectroscopy, X-ray photoelectron spectroscopy, N2 adsorption–desorption measurements, and field emission scanning electron microscopy. An electrochemical workstation was used to test the photoelectric performance of the materials. The results show that TpPa–SO3 H has –SO3 H functional groups and high photocatalytic performance for CO2 reduction. After 4 h of visible-light irradiation, the amount of CO produced is 416.61 μmol g −1 . In addition, the TpPa–SO3 H photocatalyst exhibited chemical stability and reusability. After two testing cycles under visible light irradiation, the amount of CO produced decreased slightly to 415.23 and 409.15 μmol g −1 . The XRD spectra of TpPa–SO3 H were consistent before and after the cycles. Therefore, TpPa–SO3 H exhibited good photocatalytic activity. This is because the introduction of –SO3 H narrows the bandgap of TpPa–SO3 H, which enhances the visible light response range and greatly promotes the separation of photogenerated electrons.